Greenhouse gas emissions and carbon footprint of cucumber, tomato and lettuce production using two cropping systems - Pereira, Breno de Jesus [UNESP]; Cecílio Filho, Arthur Bernardes [UNESP]; La Scala, Newton [UNESP] (Elsevier, 2021)
Vegetable intercropping is an alternative to the conventional system and characterised by a greater efficiency of land use and inputs. For this reason, it is a more sustainable and low greenhouse gas emission (GHG) cultivation model. Thus, the objective is to estimate direct and indirect GHG emissions and the carbon footprint per kilogram of vegetables produced using the intercropping and monoculture systems in a protected environment. For this, based on published studies on agronomic efficiency of these crop systems, intercropping systems of cucumber-lettuce and tomato-lettuce were compared with cucumber, tomato and lettuce monocultures. Two functional units were selected to estimate the impacts (GHG emissions) of each system (intercropping and monoculture) per 1 kg of vegetables produced and 1 ha of cultivation. The total GHG emitted for each cropping system was converted as CO2 equivalent (CO2eq), using the IPCC methodology and specific factors (Tier 2). The GHG emissions in both intercropping configurations (16,368 kg CO2eq ha−1) were about 35% lower than the total emitted in monocultures (25,273 kg CO2eq ha−1). Infrastructure and synthetic fertilisers were the main contributing sources. The carbon footprint to produce 1 kg of intercropped vegetables (0.105 kg CO2eq kg−1) was about five times lower than that in the monoculture (0.516 kg CO2eq kg−1), mainly because of the differences in crop productivities. Our results confirm that the intercropping of cucumber-lettuce and tomato-lettuce should be promoted to mitigate GHG emissions.
Keywords: CO2 equivalent; Direct and indirect emissions; Intercropping; Vegetables